IMICROBE competition: the beginning of academic tradition - Sahlan, Noraziah
In March 2025, two groups of medical students from UiTM embarked on a journey to Nilai, Negeri Sembilan, to participate in the International Microbiology Competition, IMICROBE’25, hosted by Universiti Sains Islam Malaysia (USIM). The teams, consisting of fourth- and fifth-year medical students, were accompanied by their chaperone, Dr. Siti Norbahiyah Awad from the department of Medical Microbiology and Parasitology. The group arrived at the venue at 7.30 a.m., ready for the challenge ahead.